Rectangular coordinates state estimation of electrical power system using singular value decomposition - Rakpenthai C. (2014)
This paper presents a new state estimation method based on the equivalent current measurement model and rectangular coordinate state variables. The bus voltage phasors in rectangular form are considered as the estimated states. Voltage magnitude, power measurements and estimated voltage buses are employed to find equivalent current phasor measurements. With this formulation, the measurement equation can be formulated as a linear-like system and the solution can be obtained by iterative computation using a constant gain matrix. For some system, this gain matrix may be ill-condition. To overcome the problem of ill-condition, the singular value decomposition (SVD) is employed in this work. Numerical simulation results on the IEEE 30-and 57-bus systems are compared with the conventional method based on polar form. It is found that the proposed method requires lesser computational time than the conventional method with SVD.